Analysis of various models of chronic osteomyelitis in experimental animals - Alexander Rudenko; Berik Tuleubayev; Dina Saginova; Amina Koshanova; Konstantin Vorobyov (National Scientific Medical Center, 2022)
Introduction: Chronic osteomyelitis occurs in 3-25% of cases after open fractures and in 1-8% of cases after surgical treatment of closed fractures. It accounts for 3 to 10% in the structure of purulent surgical diseases. Traditional treatment methods many times do not provide a complete cure for osteomyelitis. In modern medicine, many experimental models have been created on different types of laboratory animals in order to reproduce the model of chronic osteomyelitis and subsequently improve its therapy. Of all the experimental animals, we chose rabbits for the application of the developed method for the treatment of chronic osteomyelitis and for the selection of the optimal model of bone tissue suppuration. The objective was to conduct a clinical, radiological and histological analysis of various models of chronic osteomyelitis in experimental animals. Materials and methods: The experiment was carried out on 90 outbred rabbits. All rabbits were randomly divided into 5 groups. The rabbits were kept in a room with controlled temperature (16-21 °C) and relative humidity (45-65%). The rabbits were placed in special cages - 2-3 rabbits per each. Surgical intervention was performed under general anesthesia. Surgical access was made along the anterior surface of the distal metaepiphyseal area of the left femur. All animals were intraosseus injected with Staphylococcus aureus as an infectious agent. The development of chronic osteomyelitis was assessed by clinical, radiological, microbiological, histological and statistical methods. Results: The study showed that X-ray and histological methods play an important role in the analysis of experimental models. The signs of osteomyelitis development can be seen on the 14th day after the operation with the help of the X-ray method, while wound healing, weight and temperature cannot be indicators. According to the results of the experiment, the signs of chronic osteomyelitis developed in all 5 groups, but its activity was different. Histological examination showed that osteomyelitis developed differently in different groups, fibrosis developed unevenly.